LA OFICINA HAYS Y LAS DOS VERSIONES FÍLMICAS MODERNIZADAS DEL CASO MADELEINE SMITH: LETTY LYNTON (1932) Y DISHONORED LADY (1947) - Dra. Carmen GUIRALT GOMAR (Fonseca, Journal of Communication, 2023)
The celebrated case of Madeleine Smith, the Glasgow poisoner, who was tried for murder (and absolved) in 1857, has resulted in many novels, plays, films and television series. Hollywood, during its classical period, made two updated versions of the incident: Letty Lynton (Clarence Brown, 1932) and Dishonored Lady (Robert Stevenson, 1947). Even though the two films are separated by more than a decade, the self-censorship introduced by the studios themselves – MPPDA, commonly known as the Hays Office – exercised so much control over the two pictures that they can hardly be taken as equivalent